GROWTH INHIBITION TEST OF ECO-ENZYME AGAINTS STREPTOCOCCUS SPP. ISOLATED FROM THE ECTODERMAL TISSUE OF DOG’S SKIN - Welfalini, Sheira Tannia; Suartha, I Nyoman; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2022)
Dogs skin are susceptible to skin diseases cause by bacterial infection. Although Streptococcus spp. is a component of the normal flora of the skin, streptococcal infection can cause diseases in dogs such as abscesses, local infections, and life-threatening septicemia. Eco-enzyme fermentation products are suspected to have high antibacterial activity due to the content of acetic acid. This study aims to determine the antibacterial activity of eco-enzyme in inhibiting the growth of Streptococcus spp. using the agar well diffusion method with a completely randomized design experiment of 6 treatments and 4 trials which include eco-enzyme with concentrations of 30%, 50%, 70%, 100%, aquadest as the negative control, and Penicillin G as the positive control. The parameter measured is the diameter of the inhibition zone formed. The data were then analyzed with Analysis of Variance (ANOVA). The results of the study showed that the eco-enzyme with concentrations of 30%, 70%, and 100% were able to inhibit the growth of Streptococcus spp .